Pelatihan Pemanfaatan Aplikasi Bandicam dan Google Classroom untuk Pembelajaran Online - Widyah Noviana; Tri Hidayati; Ines Heidiani Ikasari; Ita Handayani; Dena Wulandari; Windia Hadi (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2022)
Background: The teachers of SMP Negeri 14 Tangerang still have many teachers who use Whatsapp groups as a medium for online learning, and some teachers have not been able to make learning videos and have not been able to use LMS (Learning Management System). The purpose of this service is to provide counseling and training on the use of bandicam and google classroom applications for online learning. Methods: There are three stages, namely, 1) Observation stage, location survey, a survey of problems experienced by schools, data collection of teachers to be included and signing of cooperation 2) Pre-training stage, teachers are given counseling related to google classroom and bandicam application 3) Training stage, given training on making video screen recording techniques using the bandicam application and practicing as students when in google classroom 4) Discussion stage, the service team and teachers discussed each other regarding difficulties in making videos and problems that arose during the making of video 5) Evaluation stage, the PkM team knew the obstacles and successes achieved during the activity. The number of participants amounted to 10 teachers, 5 lecturer teams, and 5 students. Result: Teachers can make learning videos using the bandicam app and can use google classroom. Conclusion: Teachers are able to understand the creation of learning videos uploaded into google classroom.